"An Old Prostitute": A Relevance Theory Analysis: (Sajak "Pelacur Tua": Analisis Teori Relevans) (Jurnal Bahasa, 2015)
Usman Awang was a Malaysian National Laureate who constantly expresses the feelings of the society in his writings. Verses in his poems were beautifully written. In his poem "Pelacur Tua" (An Old Prostitute) ways of living despite the immoralities were finely written in order not to hurt their feelings. But nevertheless, and in general, community is infuriate at individuals involving themselves in prostitution. Prostitutes' ways of living are assumed to be secretive. This research attempted to find the secrets via language. This research utilized the Relevance Theory from the field of pragmatics. This theory was founded by Sperber and Wilson in 1986. The figurative languages in Usman Awang's poem were analysed by using Relevance Theory to reveal the secrets in the life of a prostitute. This research found that there were various figurative languages used by Usman Awang in his poem that comprised of personification, hyperbole and irony. It was also found that the meanings of these figurative languages used were tacit but nonetheless, they were unequivocally or explicitly expressed. The unequivocally expressive meanings thus demanded the findings of the true meanings or implicit meanings. The different figurative languages studied were found to be hiding the emotions of prostitutes and vice versa, in general the feelings of communities towards them. Worries, unpleasantness, loneliness, exhaustion, sadness, regret, and so forth were successfully revealed in spite of the happiness and easy income earned. It was also found that by embarking on this research, a more scientific attestation can be brought forward from just merely making general statements regarding their emotions.Keywords: Explicitly, Implicit, Figurative Language, Relevance Theory, Pragmatics